2015
DOI: 10.5056/jnm15061
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ion Channels: An Important Therapeutic Implication in Gastrointestinal Dysmotility in Patients With Spinal Cord Injury

Abstract: Gastrointestinal (GI) dysmotility is a severe, and common complication in patients with spinal cord injury (SCI). Current therapeutic methods using acetylcholine analogs or laxative agents have unwanted side effects, besides often fail to have desired effect. Various ion channels such as ATP-sensitive potassium (KATP) channel, calcium ions (Ca 2+ )-activated potassium ions (K + ) channels, voltage-sensitive Ca 2+ channels and chloride ion (Cl − ) channels are abundantly expressed in GI tissues, and play an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…have suggested that release of neurotransmitters and several ion channels in GI tissues including ATP-sensitive potassium (K ATP ) channel, calcium ions (Ca 2+ )-activated potassium ions (K + ) channels, voltage-sensitive Ca 2+ channels and chloride ion channels play an important role in regulating GI motility. 4 In fact, those mechanisms have served as the fundamental knowledge in new discoveries and development of new therapeutic agents. Cholinergic agonists or laxative agents are widely used for gastrointestinal motility disorders management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have suggested that release of neurotransmitters and several ion channels in GI tissues including ATP-sensitive potassium (K ATP ) channel, calcium ions (Ca 2+ )-activated potassium ions (K + ) channels, voltage-sensitive Ca 2+ channels and chloride ion channels play an important role in regulating GI motility. 4 In fact, those mechanisms have served as the fundamental knowledge in new discoveries and development of new therapeutic agents. Cholinergic agonists or laxative agents are widely used for gastrointestinal motility disorders management.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic agonists or laxative agents are widely used for gastrointestinal motility disorders management. 4 However, these drugs have an undesirable side effect. Complementary and alternative medicines (CAM) have been associated with symptom management and quality of life in a common gastrointestinal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Mature ICCs, as shown by high levels of ramification, indicate more efficient ICCs [ 19 ]. In addition, neurotransmitters from enteric nerves activates ion channels in ICCs [ 12 ]. In the present study, ultrastructural assessment revealed significantly less colonic ICCs in SCI rats compared with sham animals.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal motility is coregulated by the central and enteric nervous systems. Upon SCI, the connection between the defecation nerve center (sacral spinal cord; S 2–4 ) and central nerve center is lost, altering the normal function of the parasympathetic nerve system and damaging motor neurons in the enteric nervous system [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation